The Effect of Internet Banking, Product Advantages, and Customer Relationship Management on Customer Loyalty at Bank Syariah Indonesia Semarang City - Wardana, Yanuar Wendy; Iqbal Reza Pratama (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: The growing significance of customer loyalty in the competitive landscape of Islamic banking underscores the need for Bank Syariah Indonesia to understand the key factors that influence it, particularly in Semarang City. Objective: This research aims to analyze the effect of Internet banking, product advantages, and customer relationship management on customer loyalty at Bank Syariah Indonesia in Semarang City. Method: A non-probability sampling technique was applied, explicitly utilizing the snowball sampling method, which started with a small initial group of respondents and expanded through referrals. The sample obtained in this research was 100 Bank Syariah Indonesia customers in Semarang City. The data were analyzed using various statistical tests, including validity and reliability checks, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression with Statistical Package for the Social Sciences (SPSS) v.26. Result: The findings show that Internet banking, product advantages, and customer relationship management positively and significantly affect customer loyalty. This study shows that Internet banking, product excellence, and customer relationship management significantly affect customer loyalty at Bank Syariah Indonesia Semarang City. These variables can explain 66.1% of the variance in customer loyalty, while other factors influence the remaining 33.9%. Implication: The impact of this research provides strategic insights for Bank Syariah Indonesia or other banks to understand better and fulfill customer needs, which ultimately can increase customer loyalty and satisfaction in the long term.